Overexpression of KCNN3 results in sudden cardiac death. (1st December 2013) - Mahida, Saagar; Mills, Robert W.; Tucker, Nathan R.; Simonson, Bridget; Macri, Vincenzo; Lemoine, Marc D.; Das, Saumya; Milan, David J.; Ellinor, Patrick T.
Abstract: Background: A recent genome-wide association study identified a susceptibility locus for atrial fibrillation at the KCNN3 gene. Since the KCNN3 gene encodes for a small conductance calcium-activated potassium channel, we hypothesized that overexpression of the SK3 channel increases susceptibility to cardiac arrhythmias. Methods and results: We characterized the cardiac electrophysiological phenotype of a mouse line with overexpression of the SK3 channel. We generated homozygote ( SK3 T/T ) and heterozygote ( SK3 +/T ) mice with overexpression of the channel and compared them with wild-type (WT) controls. We observed a high incidence of sudden death among SK3 T/T mice (7 of 19 SK3 T/T mice). Ambulatory monitoring demonstrated that sudden death was due to heart block and bradyarrhythmias. SK3 T/T mice displayed normal body weight, temperature, and cardiac function on echocardiography; however, histological analysis demonstrated that these mice have abnormal atrioventricular node morphology. Optical mapping demonstrated that SK3 T/T mice have slower ventricular conduction compared with WT controls ( SK3 T/T vs. WT; 0.45 ± 0.04 vs. 0.60 ± 0.09 mm/ms, P = 0.001). Programmed stimulation in 1-month-old SK3 T/T mice demonstrated inducible atrial arrhythmias (50% of SK3 T/T vs. 0% of WT mice) and also a shorter atrioventricular nodal refractory period ( SK3 T/T vs. WT; 43 ± 6 vs. 52 ± 9 ms, P = 0.02). Three-month-old SK3 T/T mice on the other hand displayed a trend towards a more prolonged atrioventricular nodal refractory period ( SK3 T/T vs. WT; 61 ± 1 vs. 52 ± 6 ms, P = 0.06). Conclusion: Overexpression of the SK3 channel causes an increased risk of sudden death associated with bradyarrhythmias and heart block, possibly due to atrioventricular nodal dysfunction.